The Influence of the Work Environment and Work Discipline on Elementary Teachers’ Performance - Yusnidar, Yusnidar; Azhar, Azhar; Sumarno, Sumarno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aims to analyse the effect of the work environment and work discipline on the elementary teachers’ performance. The source of data in this study was elementary teachers from Dumai, Riau province, Indonesia. The data of this study were obtained from the distribution of questionnaires to 166 elementary teachers who were selected using random sampling technique. Data analysis used multiple regression analysis. The results showed that individually and collectively work environment and work discipline had an effect on elementary teachers’ performance. A comfortable work environment and a high level of work discipline will improve teacher performance. Thus, it can be concluded that the variables of work environment and work discipline on teacher performance have a positive influence.